An Overview of Colonial and Post-colonial Punjabi Literature (Khairulummah, 2022)
his article explore the relationship between colonialism and Punjabi literature. To better understand this relationship a comparison of colonial and postcolonial Punjabi literature is presented. Colonial Punjabi Literature is influenced by the Imperial process of colonization. New themes and genres were introduced during Colonial period of Punjabi Literature. Reaction and resistance against colonizers is also a dominant theme of Punjabi literature produced during colonial period. Post-colonial writers restructured the imported colonial art-forms to assimilate the style, structure, and themes of native styles of literary expression. They expressed new themes in in literary genres introduced during colonial period. Visible changes in the style, structure and themes of Punjabi Literature are found in Post-colonial period. Overall, colonization has its positive as well as negative impacts on Punjabi Literature. Historical Background of Punjabi LiteraturePunjabi literary history is divided into four periods. Early Punjabi literature (11th-15th century), Mughal and Sikhs periods (16th century to 1857), the colonial period (1858-1947) and Post-independence literature (1947 to date). Post independence period is further divided into two categories that west Punjab (Pakistan) and east Punjab (India). This article presents a brief comparison of the two periods i.e. the Colonial period and post-independence period with focus on west Punjabi literature.The Colonial Period (1858-1947)